2015
DOI: 10.1589/jpts.27.1589
|View full text |Cite
|
Sign up to set email alerts
|

Effects of specific muscle imbalance improvement training on the balance ability in elite fencers

Abstract: [Purpose] The lunge Motion that occurs frequently in fencing training and matches results in imbalance of the upper and lower limbs muscles. This research focuses on the improvement of the imbalance that occurs in the national team fencers of the Republic of Korea through specific muscle imbalance improvement training. [Subjects] The subjects of this research were limited to right-handed male fencers. Nine male, right-handed national fencing athletes were selected for this study (4 epee, 5 sabre; age 28.2 ± 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…They showed that fencers may have performance symmetry superior to non-fencers due to an underlying high skill in bilateral control, while Poulis also advocated that elite fencers have all-round development on their neuromuscular system [ 48 ]. In fact, the risk of injury associated with asymmetry is recognized, such that balance or weight training is often introduced to tackle with possible asymmetry-induced injuries [ 54 56 ] [ 36 , 57 ]. The variation in outcome measures and training method may contribute to the inconsistency of results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that fencers may have performance symmetry superior to non-fencers due to an underlying high skill in bilateral control, while Poulis also advocated that elite fencers have all-round development on their neuromuscular system [ 48 ]. In fact, the risk of injury associated with asymmetry is recognized, such that balance or weight training is often introduced to tackle with possible asymmetry-induced injuries [ 54 56 ] [ 36 , 57 ]. The variation in outcome measures and training method may contribute to the inconsistency of results.…”
Section: Discussionmentioning
confidence: 99%
“…Training of balance and coordination is also a fundamental element [ 65 ], By taking specific balance training, fencers demonstrated better coordination (42.36% improvement in balance score) and less body sway (7.02% less in dispersion of the center of plantar pressure) in single-leg standing tasks. When coordinating touché and lunge movements, elite fencers produced higher sword velocity (2.90±0.30m/s VS 2.52±0.29m/s) and body center velocity (0.41±0.20m/s VS 0.04±0.10m/s), compared to novice fencers [ 36 , 40 ]. In their review of training programs, Turner et al [ 53 ] reported that most programs are customized to a fencer’s ability, sex and age by coaches, based on their experience or anecdotal knowledge rather than on evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, research evaluating balance in fencers has focused on their control of upright standing posture. 12,13 This largely ignores the ability of a fencer to control their balance while performing volitional movements. Two recent studies have used the SEBT, from which the YBT is derived, to evaluate dynamic balance performance in child and club-level fencers.…”
Section: Discussionmentioning
confidence: 99%
“…Another study used measures from static balance assessments to evaluate the effectiveness of a training program that addressed muscle imbalances in fencers. 13 A possible limitation of these two studies was that the balance task did not require the participant to demonstrate dynamic balance control during volitional movements, which is required during fencing.…”
Section: B Introductionmentioning
confidence: 99%
“…In this study by Kim et al, a 3 month program of stretching (dynamic and passive), pilates, and core and lower limb strengthening was used to evaluate if there was any improvement in balance of mediolateral sway of the nondominant limb. A pre-and post-test model was used, and there was a statistically significant improvement noted in mediolateral sway of the non-dominant lower extremity and improvement of balance scores [6]. Despite this benefit, there were no reports if this prevented any of the commonly cited injuries in this sport.…”
Section: Discussionmentioning
confidence: 99%